The role of tenants in the transition towards more sustainable energy consumption - Benedikt Maciosek; Mehdi Farsi; Sylvain Weber; Martin Jakob (University of Neuchâtel, Institute of Economic Research (IRENE), 2022)
The split incentive problem leads to under-investment in energy improvements of rental buildings. This prevents the large CO2 savings potential from being achieved and leads to disadvantages for tenants. New investment opportunities and a willingness of tenants to pay for investments made by the landlord have the potential to solve the problem. Against this background, the aim of this research project is to find out how the situation is perceived by tenants and what preferences and trade-offs affect their decision-making. To answer this, we conduct a discrete choice experiment (DCE) and analyse the choice behaviour of 680 Swiss tenants. Finally, we calculate their respective willingness to pay (WTP).The results show that tenants are really interested in energy investments, especially when it comes to renewable energy. Moreover, the willingness to pay for such improvements indicates that they consider the current situation to be in need of improvement. Interestingly, however, they do not value collective investment opportunities that can circumvent the split incentive problem, but are more willing to pay part of the investment costs if the landlord invests. However, they also value the purchase of renewable electricity to contribute to more sustainable consumption without the landlord's action. Their choice is also affected by net-metering and subsidy treatments, which shows that targeted policies can help to promote the willingness to contribute to such investments and ultimately reach CO2 reduction goals.
Keywords: D12; L94; Q41; 330; Energy efficiency; Renewable energy; Choice experiment; Conditional logit models